THE DISTRIBUTION OF TOXIC DINOFLAGELLATES ON SEA GRASS Enhalus acoroides AT PARI ISLAND, SERIBU ISLANDS - Riani Widiarti; Fitrian Anggraini (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2012)
Benthic dinoflagellates causing Ciguatera Fish Poisoning (CFP), could be found attached either on macroalgae or sea grasses. Research on density and distribution of benthic dinoflagellates on sea grass leaves was conducted in Pari Island waters, Seribu Islands, in April 2012. Research was carried out by collecting Enhalus acoroides leaves from each site, and put inside the plastic jars containing seawater. In order to separate the dinoflagellates species from the leaves, the plastic jars were shaken vigorously and the seawater filtered through a series of sieves (125μm and 20μm). The resulted residue was than observed using Sedgewick rafter cell under light microscope. Based on samples collected, eight benthic dinoflagellates were found, where five of them were potentially toxic. They were Prorocentrum concavum, P. lima, P. rhathymum, Ostreopsis lenticularis, and O. siamensis. The highest abundance was found in the reef flat on the southern side of the island (652 sel/cm2 seagrass leaf). Research showed that the density and distribution of toxic dinoflagellates on sea grass at Pari Island, Seribu Islands were more influenced by local water currents.Keywords: benthic dinoflagellates, Ciguatera Fish Poisoning, Pari Island, seagrass